Efficacy of Unstable Platforms offer Massive Muscle work in Establishing the Strength an Important Motor Component in Athletes Sustaining Soft Tissue Injuries in Knee - Priya, N.Hari; .Balaji, P; Pasupatham, V. (Journal of Neonatal Surgery, 2025)
Background context: Balance strength and power forms the part of motor skill which integrates the nervous system, musculoskeletal system to intervene. Strength and speed adjoin balance to perform conventional activities in sports like walking stairclimbing running jumping and recreational activities. Balance and strength become an integral part of neuromuscular complex to undermine the complex movements which becomes the basic skills in sport. A standardised rehabilitation programme utilises specific training to compensate for the deficits of musculoskeletal system following injuries while indulging in sports. An unstable platform like wobble board Bosu Ball Trampoline offers degree of difficulty to restore the components related to Athletes Skills. Objective: To determine the efficacy of unstable platform in establishing the components required for athletes in sport performance. To impose the challenges to develop the component like strength forms the part of skills in sports. Rehabilitation programme serves as the contributing factor to offer training in different platforms in Athletes sustaining soft tissue injuries in knee. Eligibility Criteria and Methodology: The design of the research relies on Randomization methods with pre and post treatment observation and recordings in the sports science and rehabilitation Department. The Randomization method has been incurred by the researcher being single blinded of unaware of the allocation of individuals in the training groups. All participants received the instructions on procedure and purpose of the training and consent received from the participant prior to exposure of the research. The participants aged 18-25 belongs to the discipline of sports science and physical Education Department. The study based on the effects of Bosu Ball training Trampoline training and Conventional training for an exploration of eight weeks. The quantification of Strength an important component of sport relies on Dynamometer. 45 athletes were identified in department of Physical Education with Grade 1 and Grade 2 ACL Injury confirmed by the investigation under the division of Orthopaedics. The Consent and approval received from the Ethical Board of Erstwhile Rajah Muthiah Medical College and Hospital for commencing the research studies. The inclusion criteria have history of ACL injury or concomitant injuries recruited in the study.The exclusion criteria include Grade 3 injuries, Balance impairment, Recurrent knee injuries, internal derangement of knee patellar dislocations and fractures. Key Points Based on Intervention: Strength and power are the major components for an athlete to return to sport participation. The protocol comprises of various training of Bosu Ball Trampoline and Conventional treatment. The muscle strength an important motor component gained through neuromuscular training on various platforms becomes the essential part of sports.